Electrospray Preparation and Microwave Absorption Properties of ATO Hollow Micro/Nanospheres. (November 2019) - Zhao, Fang; Tang, Xiangjun; Wang, Xinkun; Zhang, Sa; Duan, Rongxia
Abstract: Sb 3+ -doped SnO2 (ATO) hollow micro/nanospheres were prepared through electrospray and calcination technique. The influences of the calcination temperatures (500°C, 600°C, 700°C) on the crystal structure, micromorphology and microwave absorbing property of the calcined products were characterized by means of XRD, FT-IR, SEM and vector network analyzer. The results showed that Sb 3+ -doped SnCl2 /PVP precursor polymer were smooth spheres with diameters of around 0.35-2.1μm. The pure rutile structure of SnO2 formed at 500°C, and the Sb 3+ entered the lattice of SnO2 . When the calcination temperature is 500°C and 600°C, ATO micro/nanospheres appeared to be hollow structure, and the surface were made up of many small particles. When the calcination temperature is 700°C, the ATO grains grown up which contained in the micro/nanospheres, and lost the sphere morphology and presented the irregular granlar forms. The microwave absorption properties of ATO hollow micro/nanospheres calcined at 600°C was the best as the matching thickness was 2mm. The minimum reflectivity can reach -32dB at 10.8GHz, and the frequency band with reflectivity less than -10dB was 9.8-12.2GHz. The minimum reflectivity of ATO hollow micro/nanospheres moved to a low frequency as the matching thickness increased. When the matching thickness was 3mm, the microwave absorption peaks were double, at which the frequency band with reflectivity less than -10dB was widen.